A model for evaluating the success factors for implementation of lean manufacturing in small and medium scale enterprises. (2016) - Ramadas, T.; Satish, K.P.; Girish, T.
In recent years, the world has given attention on the progress of small and medium enterprises. Meanwhile, the world has also been looking ahead to lean manufacturing concept as a facilitator for companies to attain prosperity. Hence, it is suggested that lean can be applied to small and medium scale enterprises. However, modern SMEs are suffering to identify the key success factors for implementation of lean manufacturing. The identification of key success factor demands the need to develop the model, rather a strong model using structural equation modelling (SEM) that can enable to establish the key factors for implementation of lean manufacturing. In order to fulfil the need, a model is designed to indicate the key success factors using SEM. The results show that two constructs named as managerial, and structure factors of SMEs has a significant role in the lean implementation.